A coherent framework for understanding critical success factors of ICT project environment - Subiyakto, A'ang; Ahlan, Abdul Rahman (2013)
Although there has been significant research on information and communication technology (ICT) project success, but there are still gaps around this field. Thus, further understanding to ensure the level of ICT project success is still required in both theory and practice. The ultimate aim of this study is develops a coherent critical success factors (CSFs) framework for helping ICT project managers to deal with the complexity of project dimensions which have influenced the shaping of project success. The four consideration points in this framework development are: first, based on a comprehensive success definition as guidance for measuring the critical connection between the success criteria level and the CSFs level; second, integrating coherently four project dimensions for encouraging the high content validity; third, presenting the alternating critical connection between the project success definition and the CSFs determination; lastly, adopting the project stakeholder perceptions from multiple levels of an ICT project organization’s environment. However, it is a proposition concept, but this proposed CSF framework is reasonable in the context of the ICT project success improvement.